Transfusão de coca cola: a contingência da cultura pop na obra de Roberto Drummond e nas telas de Rubens Gerchman - Ernest Christian Bowes Junior (2015)
This comparative study proposes an analysis of Roberto Drummond's works, specifically Sangue de Coca-cola, a novel that integrates his ''Coca-Cola circle'', along with what is presented in Rubens Gerchman's trajectory, from the 1960's on, an artist who narrates the Brazilians in a figurative way, subdued by the mass production and its consequential mythology. This study acknowledges that both were led by popular movements over questioning a political period that was the 1960 decade, reflected through common themes as the crowd, soccer, eroticism and carnaval. Thereby, they started to disturb a decade in virtue of such aesthetic and, although being distinct products, they share the same enthusiasm: the pop art. The study considers that pop art is not static and that it materializes itself through the interaction with other media and with culture. Under this premises, it is relevant to look at the contingency of pop literature as a precedent of: modern literature, some artistic movements from the end of the 19th century and the beginning of the 20th century, the industrial production and of labor, within the means of mass communication. To designate Coca-Cola as the maximum representation of the North American cultural empire and of the globalized tendencies of the post-modern men, the study constitutes literature and pop art as an appropriate territory for thought concerning the contemporary behavior. Therefore, the transit between distinct discursive fields as Philosophy, Sociology and Literary Theory was presented, then, as the most suitable strategy for this discussion.